(untitled) (Nuntius Antiquus, 2009)
In this paper, we intend to report the process of a translation proposal, developed from translation theoretical studies applied to dramatic texts from the V century B.C theater in Athens. Among many texts that are currently available, we chose the tragedy Persians, by the greek author Aeschylus. In the process, which happened in a seminar of Greek language and literature, where we did the instrumental translation in class and, a posteriori, individually, the students gave to the translation an established format with scenic and aesthetic concerns. Each student reports in this article his/her experience and his/her focus of interest; finally, we offer a translation tested by actors and directors and presented orally in class with a relative success.